Pemberdayaan Kelompok Sadar Wisata (POKDARWIS) Dalam Pengembangan Objek Wisata Pantai Sasak Pohon Seribu di Kabupaten Pasaman Barat - Hendri, Rahma; Wahyuni, Nila; Ariany, Ria (Journal of Administration, Governance, and Political Issues, 2026)
The purpose of this describe the empowerment of tourism awareness groups (Pokdarwis) in the development of the Sasak Pohon Seribu Beach tourist attraction in West Pasaman Regency. This research is motivated by the important role of local communities in community-based tourism management to improve economic welfare while preserving the environment and culture. Although Sasak Pohon Seribu Beach is a leading regional tourist destination in West Pasaman, its management still faces challenges such as low community participation, limited human resources, and a lack of innovation in tourism developmen.The method used in this study was descriptive qualitative. Data collection techniques included interviews, observation, and documentation. This study used Edi Suharto’s empowerment approach with the 5Ps: enabling, strengthening, protection, supporting, and maintaining.The results show that the empowerment of Pokdarwis in the development of the Sasak Pohon Seribu Beach tourist attraction in West Pasaman Regency has been successful in terms of enabling, strengthening, protecting, and supporting aspects, through outreach activities, training, and mentoring. However, maintenance remains weak due to inadequate ongoing mentoring and training, as well as minimal monitoring  and  evaluation  of  Pokdarwis  and  community development.